Les avatars des économies de marché - Joyal, André (Études internationales, 1981)
The difficulties experienced by the Western economies since the middle seventie have given rise to considerable debate among economists. Some, referring to structural changes in the way the economy functions, have no hesitation in speaking of an economic crisis, while others, less pessimistic, consider that the present economic problems are due to the concordance of particular circumstances. The latter, evidently, belong to the dominant current of thought. Within this group we find some old ideas being put forward once more, challenging the various means of State intervention to regulate the economy.The relevance of treating the present situation as one of economic crisis is dealt with here in the light of four inter-related factors : the fall in labor productivity, the slowdown of the impact of technology, fordism, and the profitability of capital. A reconsideration of traditional economic policies brings out the need to accept the requirements of slower economic growth. Many persons have already adopted their consumer behavior to this new situation.